2011
DOI: 10.3390/nu3040429
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrition Transition in Africa: Can It Be Steered into a More Positive Direction?

Abstract: The objective of this narrative review is to examine the nutrition transition and its consequences when populations in Africa modernize as a result of socio-economic development, urbanization, and acculturation. The focus is on the changes in dietary patterns and nutrient intakes during the nutrition transition, the determinants and consequences of these changes as well as possible new approaches in public health nutrition policies, interventions and research needed to steer the nutrition transition into a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(188 citation statements)
references
References 27 publications
9
179
0
Order By: Relevance
“…The THUSA study revealed decreased consumption of staple foods and plant-based proteins and increased consumption of energy dense snack-based foods, sweetened carbonated beverages, red meat, fast foods, and convenience foods. 13 The nutrition transition in Africa is occurring along with the demographic (a shift from high mortality to improved lifestyle and health status) and epidemiologic (a change in disease pattern from infectious to chronic degenerative diseases) transitions. 14 The simultaneous occurrence of the demographic and epidemiologic transitions together with the nutrition transition contributes to the increasing shift towards obesity and diet-related noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The THUSA study revealed decreased consumption of staple foods and plant-based proteins and increased consumption of energy dense snack-based foods, sweetened carbonated beverages, red meat, fast foods, and convenience foods. 13 The nutrition transition in Africa is occurring along with the demographic (a shift from high mortality to improved lifestyle and health status) and epidemiologic (a change in disease pattern from infectious to chronic degenerative diseases) transitions. 14 The simultaneous occurrence of the demographic and epidemiologic transitions together with the nutrition transition contributes to the increasing shift towards obesity and diet-related noncommunicable diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As articulated by Popkin (6) , Popkin and Gordon-Larsen (7) and supported by others, nutrition transition develops over time and has five fairly distinct phases, but most countries are between phases 3 and 5 (6)(7)(8) (Fig. 1).…”
Section: What Is the Nutrition Transition?mentioning
confidence: 80%
“…When populations modernize as a result of socio-economic development, urbanization and acculturation as is observed in SA, it is characterized by changes in dietary paterns and nutrient intakes that increase the risk of the diet-related non-communicable diseases [9]. Non-communicable diseases have emerged in Sub-Saharan Africa at a faster rate and at a lower economic level than in industrialized countries before the batle against under-nutrition could be won.…”
Section: The Status Of Food and Nutrition Security In South Africa (Cmentioning
confidence: 99%